2016
DOI: 10.1007/s00192-016-2980-1
|View full text |Cite
|
Sign up to set email alerts
|

Traction force needed to reproduce physiologically observed uterine movement: technique development, feasibility assessment, and preliminary findings

Abstract: Introduction and hypothesis This study aimed to describe a novel strategy to determine the traction forces needed to reproduce physiologic uterine displacement in women with and without prolapse. Methods Participants underwent dynamic stress magnetic resonance imaging (MRI) testing as part of a study examining apical uterine support. Physiologic uterine displacement was determined by analyzing uterine location in images taken at rest and at maximal Valsalva. Force-displacement curves were calculated based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…9 For example, only a small traction force (3 oz., or the weight of a large chicken egg) is needed to cause the amount of displacement seen physiologically during maximal Valsalva in MRI. 10 This observation is consistent with the hypothesis that the levator ani muscles act to close the pelvic floor so that increases in intraabdominal pressure do not result in a downward force on the ligaments. 11,12 This is also consistent with a “slack-cord” paradigm, where movement of the uterus near its normal location is determined by the status of the pelvic floor, with the apical ligaments playing a larger role once greater degrees of descent occur.…”
Section: Commentsupporting
confidence: 90%
“…9 For example, only a small traction force (3 oz., or the weight of a large chicken egg) is needed to cause the amount of displacement seen physiologically during maximal Valsalva in MRI. 10 This observation is consistent with the hypothesis that the levator ani muscles act to close the pelvic floor so that increases in intraabdominal pressure do not result in a downward force on the ligaments. 11,12 This is also consistent with a “slack-cord” paradigm, where movement of the uterus near its normal location is determined by the status of the pelvic floor, with the apical ligaments playing a larger role once greater degrees of descent occur.…”
Section: Commentsupporting
confidence: 90%
“…These veins contain no valves (Batson, 1940), indicating that the paracolpium can rapidly reduce its volume upon a small increase in external pressure. These findings appear to explain the 'slack cord' paradigm of DeLancey cum suis, who observed that the force necessary to displace the uterus over a distance as observed upon a Valsalva maneuver was unexpectedly small (Smith et al 2013;Swenson et al 2016). In fact, these observations strongly suggest that the large veins in the paracolpium are responsible for the absorbance of acute increases in intra-abdominal pressure, such as occur during coughing.…”
Section: The Supports Of the Vagina And Uterusmentioning
confidence: 76%
“…; Swenson et al. ). In fact, these observations strongly suggest that the large veins in the paracolpium are responsible for the absorbance of acute increases in intra‐abdominal pressure, such as occur during coughing.…”
Section: Discussionmentioning
confidence: 98%
“…42 Using these data, it can be estimated that vivo stiffness is 650 times less than seen in traditional testing. 43 Preconditioning is performed during traditional material properties testing wherein the tissue is tensioned a few times before testing is measured. 44 Since the cardinal ligaments have a lattice-like arrangement 36 , it seems likely that this preconditioning straightens the fibers so that they are all aligned, making the material properties much stiffer than would be seen when loaded in vivo, where the lattice work is open as it is during life.…”
Section: Levator Ani Musclementioning
confidence: 99%